Energy Band Alignment of Few-Monolayer WS2 and WSe2 with SiO2 Using Internal Photoemission Spectroscopy. (26th August 2020) - Delie, Gilles; Litwin, Peter M.; McDonnell, Stephen J.; Chiappe, Daniele; Houssa, Michel; Afanas'ev, Valeri V.
Abstract : Internal photoemission spectroscopy was used to determine the valence band top energy position in few-monolayer WS2 and WSe2 films directly synthesized on top of the SiO2 insulator. It is found that in WS2 the valence band top edge lies systematically higher (by 0.4–0.7 eV) in energy than that in WSe2 . This unexpected trend is seen for several synthesis methods suggesting it to be the intrinsic property of these W-based layered dichalcogenides. At the same time, a change in the WS2 synthesis method from metal sulfurization to chemical vapor deposition leads to a ≈0.3 eV barrier change indicating a non-negligible impact of interface charges or dipoles. The influence of synthesis chemistry on the WSe2 /SiO2 interface barrier appears to be marginal at least for the selenization and molecular-beam epitaxy growth methods.